Determinants of Parents’ School Choice and Its Implications on Student Occupancy: Evidence from Private Schools - Taruna, Johannes Agus; Harianto, Eric (Newinera Publisher, 2025)
Increasingly intense with the growing number of educational options available to parents. This study aims to identify the key factors influencing parents’ decisions in selecting schools while linking these factors to student occupancy rates as an indicator of institutional sustainability. The research employs an Explanatory Factor Analysis (EFA) involving 113 parent respondents from Super Brilliant Kidz (SBK Center) and My School Palembang. The research instrument consists of 48 statement items that were tested for validity and reliability, yielding a Cronbach’s Alpha of 0.914, which indicates a very high level of internal consistency. The analysis revealed four dominant factors school quality and excellence, school reputation and image, cost and accessibility considerations, and religion and moral values which together explain 41.98% of the variance. The findings emphasize that teacher quality, school reputation, cost transparency, and value-added programs must be consistently maintained across all levels to strengthen student retention. Theoretically, this study contributes by linking school-choice factors with student occupancy sustainability, while practically offering insights for private school administrators in Palembang to design strategies for enhancing competitiveness.